An investigation into the characteristics and function of the phosphorylation of the cholinergic receptor - Carstens, Machteld Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Phil.(Medical biochemistry)) - University of Stellenbosch, 1981.